Early Childhood Educator Mental Health: Performing the National Quality Standard. Issue 4 (December 2017) - Corr, Lara; Cook, Kay; LaMontagne, Anthony D.; Davis, Elise; Waters, Elizabeth
IN EARLY CHILDHOOD EDUCATION and care (ECEC) settings, the mental wellbeing of educators is likely to be crucial to delivering high-quality care. Hence, this paper uses a contextual understanding of educators' mental health, and its evaluation by both educators and management, to reveal areas of the National Quality Framework that require critical revision. Drawing on Hochschild's (2012) theory of emotional labour, we report on the analysis of semi-structured interviews with family day care educators (n = 16) and ECEC sector key informants (n = 18). Results demonstrate widespread belief that educator mental wellbeing affects care quality and the children attending care. In response to job stressors and perceived surveillance, educators use emotional labour to hide negative feelings and manage risks associated with low mental wellbeing. In this context, making individual educators fully responsible for performing good mental health to meet the National Quality Standard may increase job stress and emotional labour, further distancing the aims of high-quality care. Our findings suggest that revising the NQS to improve working conditions, and addressing educator mental wellbeing are essential approaches for supporting high-quality ECEC practice.